BOOK REVIEWS (Journal of Finance, 1977)
Book reviewed in this article: Commercial Banking . By E dward W. R eed , R ichard V. C otter , E dward K. G ill , and R ichard K. S mith . Solvency and Regulation of Banks . By J ack R evell . Fundamentals of Investing . By B en B ranch . Financial Decision Making: Concepts, Problems and Cases . By J ohn J. H ampton . Financial Administration . By C lifton H. K reps , J r . and R ichard F. W acht . Money: Whence It Came, Where It Went . By J ohn K enneth G albraith . Money, Banking, and Economic Analysis . By T homas D. S impson . Money and Banking, An Introduction To The Financial System . By T homas E. V an D ahm . Financing the New Federalism ( Revenue Sharing, Conditional Grants and Taxation ). Edited by W allace E. O ates . Local Government Finance . By A lan W alter S teiss . Studies in Selective Credit Policies . Edited by I ra K aminow and J ames M. O'B rien . A Theory of Profits . By A drian W ood .